Economic development in Africa report 2017 : tourism for transformative and inclusive growth (UN New YorkUS, 2017)
Posits that Africa should adopt policies that strengthen intersectoral linkages, boost intraregional tourism and promote peace, to better harness the potential of the tourism sector to contribute to inclusive grouth, structural transformation and achievement of the Sustainable Development Goals.
Keywords: ECONOMIC DEVELOPMENT